2021
DOI: 10.21203/rs.3.rs-141578/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 ARDS is characterized by a dysregulated host response that differs from cytokine storm and is modified by dexamethasone

Abstract: We performed comparative lower respiratory tract transcriptional profiling of 52 critically ill patients with the acute respiratory distress syndrome (ARDS) from COVID-19 or from other etiologies, as well as controls without ARDS. In contrast to a cytokine storm, we observed reduced proinflammatory gene expression in COVID-19 ARDS when compared to ARDS due to other causes. COVID-19 ARDS was characterized by a dysregulated host response with increased PTEN signaling and elevated expression of genes with non-can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
(46 reference statements)
2
34
1
Order By: Relevance
“…In contrast, we found that T cells from patients who later developed VAP expressed lower levels of IFNγ at the time of intubation. This difference may relate to species-specific variations in immune signaling or intrinsic differences in the host response to influenza virus versus SARS-CoV-2 (14, 18) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, we found that T cells from patients who later developed VAP expressed lower levels of IFNγ at the time of intubation. This difference may relate to species-specific variations in immune signaling or intrinsic differences in the host response to influenza virus versus SARS-CoV-2 (14, 18) .…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 viral load correlates with interferon stimulated gene expression (14, 18) and thus we initially hypothesized that differences in viral load between groups might relate to individual VAP susceptibility. However, we found no difference between groups at the “early” timepoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that LIFR is required for lung protection during pneumonia, for example, in respiratory syncytial virus infections (RSV) [31][32][33][34] . Furthermore, its ligand, LIF, is one of the cytokines in the IL-6 family and is increased in the lungs of patients with ARDS 35,36 , which has been observed in COVID-19 patients 2,37,38 . Notably, because the D614G variant is located within the SARS-CoV-2 ITIM, the mutational distance between the LIFR ITIM and the corresponding ITIM sequence in D614G viruses increases from 2 to 3 which could reduce the potential molecular mimicry or subversion of LIFR by the D614G associated ITIM.…”
Section: Spike Protein Contains a Potential Human Immunoreceptor Tyrosine-based Inhibitory (Itim) Motif With High Similarity To An Itim Smentioning
confidence: 97%
“…Coronavirus disease 19 (COVID-19) patients exhibit varying degrees of immune system dysfunction including potential cytokine storms 1 , acute respiratory distress syndrome (ARDS) 2 and the production of autoantibodies against several self-antigens [3][4][5] . This implicates dysregulation of immune homeostasis and self-tolerance in the pathology of the disease, an area that remains understudied.…”
Section: Introductionmentioning
confidence: 99%